2004
DOI: 10.1167/iovs.04-0300
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular Sequestration of Hetero-oligomers Formed by Wild-Type and Glaucoma-Causing Myocilin Mutants

Abstract: Formation of heteromeric WT/mutant complexes may provide a critical mechanism by which mutant myocilin polypeptides produce autosomal dominant open-angle glaucoma. The intracellular sequestration of abnormal WT/mutant complexes could lead to the malfunction of MYOC-expressing cells and to POAG potentially involving a dominant negative effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
85
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(88 citation statements)
references
References 43 publications
3
85
0
Order By: Relevance
“…Studies of both cell culture and human tissue have shown that the abnormal protein that is produced by myocilin mutations is poorly secreted and is retained within trabecular meshwork cells. [37][38][39][40] Accumulation of abnormal myocilin protein may be toxic to trabecular meshwork cells and may lead to their dysfunction or death, which may ultimately produce decreased aqueous outflow, elevated IOP, and glaucoma. 41,42 Animal models harboring myocilin mutations have been developed and are beginning to reveal the specific molecular steps that lead from mutations in myocilin to the elevated IOP that is characteristic of myocilin-related glaucoma.…”
Section: Myocilin (Myoc Omim #601652)mentioning
confidence: 99%
“…Studies of both cell culture and human tissue have shown that the abnormal protein that is produced by myocilin mutations is poorly secreted and is retained within trabecular meshwork cells. [37][38][39][40] Accumulation of abnormal myocilin protein may be toxic to trabecular meshwork cells and may lead to their dysfunction or death, which may ultimately produce decreased aqueous outflow, elevated IOP, and glaucoma. 41,42 Animal models harboring myocilin mutations have been developed and are beginning to reveal the specific molecular steps that lead from mutations in myocilin to the elevated IOP that is characteristic of myocilin-related glaucoma.…”
Section: Myocilin (Myoc Omim #601652)mentioning
confidence: 99%
“…30,31 Such detergent-insoluble MYOC aggregates cannot be secreted by the cells. 30,31 In the present work, we generated CHO-K1 and HEK293 cells stably expressing C-terminal GFP-tagged WT or mutant MYOC to initially verify the effect of an additional transient expression of FLAG-tagged WT MYOC on the solubility and secretion of the formed MYOC complexes. In previous studies, it was shown that MYOC tagged with GFP was secreted with a similar efficiency as MYOC without any tag.…”
Section: Heteromeric Complexes Of Wt and Mutant Myoc Form Rough Er-dementioning
confidence: 99%
“…21,28,29 In agreement with this, several missense and truncated mutant MYOCs have been shown to interact with WT MYOCs to form heteromeric protein aggregates resulting in a block of secretion of WT MYOCs as well. 25,30,31 MYOC-secreting TM cells are phagocytotically active and keep the outflow drainage along the TM clean of deposits of particulate matter of various origin. 7,[32][33][34] We reasoned that a disturbance of the phagocytotic capacity of the TM cell population could be a pathogenetic factor in the development of MYOC-caused POAG.…”
mentioning
confidence: 99%
“…The identity of the constructs was confirmed by sequencing. Wild-type myocilin cDNA and four myocilin mutants (P370L, Y437H, I477N, and N480K) were cloned into the pRcCMV vector 30 and were kindly provided by Dr. V. Raymond (Molecular Endocrinology and Oncology Research Center, Laval University Hospital Research Center, Qué bec City, Qué bec, Canada).…”
Section: Plasmidsmentioning
confidence: 99%